A Journey to Disillusionment - Sherbaz Khan Mazari (Karachi Oxford University Press, 1999)
Chronicle of political history of Pakistan; memoirs of a prominent Pakistani politician from 1964-1988.
Include Pictures, Epilogue, Glossary and Index
Keywords: Politics and government -- Politicians -- Sherbaz Khan Mazari